Peran Pekerja Sosial Dalam Penanganan Pecandu Narkoba Di Panti Rehabilitas Narkoba Medan Plus - Sani Susanti; Khadijah Tussolihin; Thomas Ridoansih; Oriza Salsabila; Marisa Nabila; Delli Suci Ananda; Fatma Amelia (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
This research aims to determine the role of social workers (Peksos) in overcoming narcotics problems in Medan Plus. Social workers act as companions, in line with that social workers are involved in the process which includes initial approach, assessment, placement in the program, and implementation of program services. The initial approach, as a first step, is directed at identifying the need for service programs that are appropriate to the client's target conditions. Social workers also play a role in obtaining support and assistance. As intermediaries in social services, social workers have a responsibility to understand the various resources, types of services, and programs available within the scope of their duties. In addition, social workers act as rehabilitation facilitators which include facilitating the process of individual, group and community change, as well as functioning as agents of change by providing the necessary time, thought and resources. Social workers also act as motivators to provide reinforcement and motivation to clients who are victims of drug coverage in Medan Plus.